Investigating spatio-temporal surface urban heat island growth over Jaipur city using geospatial techniques. (July 2018) - Mathew, Aneesh; Khandelwal, Sumit; Kaul, Nivedita
Highlights: A new index, UHIindex, has been introduced, to study UHI effect by combining data of long period. UHIindex can be utilized to compare UHI effect of same city as well as that of different cities. Hot spots are the locations where consistently high temperatures are observed. Transect method has been carried out to analyze the change in UHI effect over a period of time. UHIindex and Transect method can be combined to observe the pattern of change in area under HS. Abstract: Urban heat island (UHI) effect is one of the major impacts at local scale. A criterion based on UHIindex and transect methods have been proposed to estimate the spatio-temporal surface UHI (SUHI) growth. The study has been carried out to analyze the spatial and seasonal variations of SUHI growth over Jaipur city of the years from 2003 to 2015 for six years' time interval using Moderate Resolution Imaging Spectroradiometer (MODIS) data. Analysis of land surface temperature (LST) data shows that significant SUHI growth exists over the study area. UHIindex has been used to mark the locations of hot spots (HS) of Jaipur city. Significant increase of up to 230% in the area of HS has been observed between 2003 and 2015. Main focus of the research is to find the increase in area, over a period of time, for fixed temperature gradient from the LST of HS. This increase in area can be used as a measure to indicate UHI growth of the city. Isothermal lines representing fixed temperature difference with respect to LST of HS have been created. Increase in area enclosed by different isothermal lines varies from 20% to above 400% during different seasons between 2003 and 2015.